Seasonal Nutrient Variation in Foliage and Leaf Litter and their Conservation in Dalbergia sissoo Ecosystems - Bisht, Smita; Negi, Mridula; Negi, J. D. S. (Indian Forester, 2003)
Monthly foliage and leaf litter nutrient content (N, P, K, Ca and Mg) were studied along with leaf fall pattern to understand the nutrient conservation in natural and plantation ecosystems of Dalbergia sissoo. It was observed that elevated concentration of Nitrogen in foliage and leaf litter along with sandy soils and high percentage of nutrient withdrawal indicated suitability of site for D. sissoo. Manmade or natural disturbances may alter soil physico-chemical properties, especially enrichment of soil with clay, to create situations favourable for secondary successional species eliminating D. sissoo.